Colombia : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
In recent years, Colombia has found several innovative ways to improve the efficiency of its public enterprise sector. One option used by Colombia to reform public enterprises has been to enhance their commercial orientation and limit the fiscal risk. If a public enterprise is considered commercially run, it could be removed from the country's fiscal indicators and targets. This paper presents the IMF staff's evaluation of these two enterprises. It also discusses the commercial orientation and fiscal risk of Isagen and Ecopetrol, respectively.